PEMANFAATAN CAIRAN ISI RUMEN SAPI DAN SAMPAH ORGANIK DALAM MEMPRODUKSI BIOGAS SEBAGAI PENGEMBANGAN HANDOUT BIOLOGI - Darmawati "; Imam Mahadi; Geny Meiry Sukma (Biogenesis, 2015)
ABSTRACTThis study was conducted to determine the effectiveness of the addition of the cow rumen fluid content of organic waste in producing biogas as a handout biotechnology development in the field of animal husbandry in the high school class XII., The study was conducted in March-April 2015.This research was carried out by two phases: biogas production using experimental research and development stage handout. Experimental study was conducted using completely randomized design (CRD), which consists of 4 treatments and 3 replicates in order to obtain 12 experimental design. If there is a difference between treatments meal test Duncan Multiple Range Test (DMRT) at 5%. The parameters observed biogas volume, pH dan temperature. The addition of the cow rumen fluid content of 250 ml best produce biogas. Where produce biogas volume as much as 447.68 cm³, pH 6, the temperature of 35ºC. Results of the study was developed as a handout that the material application of biotechnology in the field of animal husbandry.Key Words: biogas, fluid rumen cows, handout, trash organic  biogas, fluid rumen cows, handout, trash organic